High-thermal-conductivity high-temperature phase change heat storage ceramic and preparation method thereof

Through hydrothermal reaction and 3D laser printing technology, AlN-covered high-temperature phase change heat storage ceramics are formed, which solves the leakage problems and molding problems of metal phase change materials during the high-temperature phase change process, and achieves high thermal conductivity and high latent heat and ceramic preparation of complex structures, suitable for the field of thermal management.

CN119187603APending Publication Date: 2024-12-27WUHAN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411278870.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The leakage problems and molding problems of existing metal phase change materials during high-temperature phase change have led to the failure of their application performance in the field of thermal management.

Method used

Aluminum powder or aluminum-based alloy powder is used to form carbon balls/boehmite coated through hydrothermal reaction, and then impregnate in the iron sol to form AlOOH/C/FeOOH microcapsule precursor, and molded by 3D laser printing, combining nitrogen atmosphere and The catalyst generates a highly thermally conductive AlN coated structure to achieve high-temperature phase change heat storage of ceramics.

Benefits of technology

The preparation of high-thermal conductivity and high-temperature phase-change heat storage ceramics has large phase-change latent heat, excellent thermal conductivity and complex structure preparation capabilities, which reduces production costs and improves raw material utilization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119187603A_ABST
    Figure CN119187603A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of phase change heat storage ceramics, in particular to a high-thermal-conductivity high-temperature phase change heat storage ceramic and a preparation method thereof. The preparation method comprises the following steps: S1, carrying out surface treatment on aluminum powder or aluminum-based alloy powder to obtain a microcapsule precursor; s2, uniformly mixing the microcapsule precursor obtained in the step S1 with an aluminum-containing binding agent to obtain a mixed raw material; s3, performing 3D laser printing on the mixed raw material in a nitrogen atmosphere to obtain a sample; and S4, placing the sample in an N2 atmosphere, carrying out heat treatment, and then cooling. The phase change heat storage ceramic is prepared in a selective laser sintering 3D printing forming mode, the raw material utilization rate is increased, the production cost is reduced, the phase change heat storage ceramic of any complex structure can be prepared, and the high-thermal-conductivity high-temperature phase change heat storage ceramic improves the efficiency of the heat storage / release process, and is suitable for large-scale production. The high heat storage density of the phase change heat storage ceramic is effectively guaranteed, and the mechanical property of the phase change heat storage ceramic meets the requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of phase change heat storage ceramics, and in particular to a high thermal conductivity and high temperature phase change heat storage ceramic and a preparation method thereof. Background Art

[0002] As devices gradually develop towards miniaturization and precision, traditional sensible heat storage materials such as cordierite and corundum have low heat storage density and large temperature fluctuations during heat storage, which can no longer meet the development needs of modern industry. Phase change thermal storage materials have the advantages of high heat storage density and stable temperature during phase change, and have become a hot topic in the energy field in recent years. Among them, metal phase change materials have broad application prospects in the field of thermal management due to their high thermal conductivity, large latent heat of phase change, high phase change temperature, and environmental friendliness. In order to solve the leakage problem of metal phase change materials during high-temperature phase change, they need to be encapsulated. Previous technologies have mainly studied the preparation of metal microcapsules, such as:

[0003] The patented technology of "A high-temperature phase-change heat storage microcapsule based on aluminum silicon alloy and its preparation method" (CN 108300426A) is to mix aluminum silicon alloy powder, aluminum chloride and ethyl acetate in proportion, add a mixed solution of aluminum silicon alloy powder and anhydrous ethanol under stirring in a water bath, and then add a mixed solution of aluminum silicon alloy powder and acetic acid, and filter, wash, dry and sinter to obtain a high-temperature phase-change heat storage microcapsule based on aluminum silicon alloy. "A large-diameter phase-change heat storage particle and its preparation method" (CN

[0004] 109796937A) patented technology, the aluminum silicon alloy powder is washed alternately with acid and deionized water, or with alkali and deionized water, and dried at 60-200°C in a protective atmosphere to obtain surface-modified aluminum silicon alloy powder; the surface-modified aluminum silicon alloy powder is then placed in a high-temperature atmosphere furnace, and after high-temperature sintering, large-diameter phase change thermal storage particles are obtained. Current research shows that microcapsule coating technology is relatively mature, but achieving the finalization of microcapsules is still a problem.

[0005] In order to achieve the shaping of metal-based phase change materials, the patented technology of "A metal ceramic with phase change heat storage function and its manufacturing method" (CN201310293700.X) uses aluminum silicon alloy powder and corundum powder as raw materials, and prepares metal phase change heat storage ceramics through traditional forming methods such as pressing. The prepared phase change heat storage ceramics do not fully utilize the advantages of metals due to the phase change latent heat and thermal conductivity, and their performance does not have the advantages of application in the field of thermal management. Summary of the invention

[0006] The purpose of the present invention is to address the above-mentioned deficiencies of the prior art and propose a high-thermal-conductivity, high-temperature phase-change thermal storage ceramic and its preparation method with simple preparation process, low cost and easy industrial production. The prepared phase-change thermal storage ceramic has large phase change latent heat, good thermal conductivity, high raw material utilization rate, and can prepare phase-change thermal storage ceramics with any complex structure.

[0007] A method for preparing a high thermal conductivity and high temperature phase change thermal storage ceramic of the present invention comprises the following steps:

[0008] S1, adding aluminum powder or aluminum-based alloy powder to glucose solution, and hydrothermally reacting in a reactor at 160-200° C. for 2-8 hours to obtain carbon ball / boehmite-coated metal micropowder;

[0009] The metal powder coated with carbon sphere / boehmite is immersed in 60°C iron sol for 1 to 5 hours, and then the excess iron sol is removed, and the AlOOH / C / FeOOH coated microcapsule precursor is obtained by filtration and drying;

[0010] S2, mixing the microcapsule precursor obtained in step S1 and the aluminum-containing binder uniformly to obtain a mixed raw material;

[0011] S3, printing the mixed raw materials into samples by 3D laser in a nitrogen atmosphere; the laser power is 30-150W, the scanning speed is 500-5000mm / s, and the scanning interval is less than the laser radius;

[0012] S4. Placing the sample in a N2 atmosphere for heat treatment and then cooling it to obtain the high thermal conductivity and high temperature phase change heat storage ceramic.

[0013] Furthermore, the heat treatment in step S4 is to increase the temperature at a heating rate of 5°C / min, keep the temperature at 650-1200°C for 3-24h; and then cool to room temperature at a cooling rate of -5°C / min.

[0014] Furthermore, the mixed raw material also includes a catalyst.

[0015] Furthermore, the catalyst includes one or more of ammonium chloride, nano iron powder, ferrosilicon nitride, and platinum powder.

[0016] Furthermore, the mass ratio of the microcapsule precursor, the aluminum-containing binder and the catalyst is 70-99:1-30:0-3.

[0017] Furthermore, the aluminum-containing binder includes one of aluminum powder or aluminum-based alloy powder.

[0018] Furthermore, the aluminum-containing binder is aluminum silicon decamagnesium.

[0019] Furthermore, the particle size of the aluminum powder or aluminum-based alloy powder is 40 to 53 μm.

[0020] Furthermore, the particle size of the aluminum-containing binder is 15 to 53 μm.

[0021] Furthermore, the content of Si in the aluminum-based alloy powder is 10-12 wt %.

[0022] A high thermal conductivity, high temperature phase change heat storage ceramic prepared by the above preparation method.

[0023] The present invention performs surface treatment on aluminum powder or aluminum-based alloy powder to obtain a microcapsule precursor with a shell of AlOOH / C / FeOOH. The microcapsule precursor is then mixed with an aluminum-containing binder and molded using a new molding method, 3D printing. The prepared thermal storage ceramic has the following advantages:

[0024] (1) Large latent heat of phase change: Aluminum nitride whiskers coated with metal micropowder form high-temperature phase change heat storage microcapsules with high thermal conductivity. During the 3D printing process, nitrogen is introduced as a protective gas and a reaction gas. Under the action of a laser heat source, C in the shell of the microcapsule precursor reduces AlOOH and FeOOH to Al and nano-Fe. The added aluminum-containing binder promotes the sintering of the raw materials. The added catalyst and the reduced nano-Fe in the shell simultaneously promote the reaction of aluminum with nitrogen to in-situ generate AlN with a high thermal conductivity on the surface of the microcapsule precursor. The AlN generated by the reaction is coated on the surface of the raw aluminum-silicon alloy, and further coats and encapsulates the aluminum powder or aluminum-based alloy powder to prevent it from leaking due to heat. The AlN generated above is partly Al reduced from AlOOH by C in the shell of the microcapsule precursor and reacts with nitrogen to generate AlN coated on the surface of the raw aluminum powder or aluminum-based alloy powder, and partly when the laser temperature exceeds the phase transition temperature of the aluminum powder or aluminum-based alloy powder, a small amount of Al in the core may be converted into Al vapor. This part of the aluminum vapor reacts with nitrogen under the action of the catalyst to generate AlN and crystallizes on the surface of the microcapsule precursor as the temperature decreases, and further coats the aluminum powder or aluminum-based alloy powder.

[0025] (2) High thermal conductivity, good thermal shock stability and thermal cycle stability: The microcapsules are combined through the aluminum nitride whiskers generated between the particles to form a denser metal composite ceramic. Due to the short laser action time, aluminum cannot fully react with nitrogen, so there is still unreacted Al in the ceramic blank formed by laser printing in nitrogen atmosphere. The Al in the blank is further reacted with nitrogen through the subsequent nitrogen atmosphere heat treatment. At this time, the generated AlN is located in the gaps of the ceramic blank. The gaps in the ceramic blank are connected and filled with high thermal conductivity AlN, which improves the density of the ceramic sample and is crucial to improving the thermal and mechanical properties of the ceramic sample.

[0026] (3) The present invention forms phase change thermal storage ceramics through selective laser sintering, a 3D printing molding method, which improves the degree of automation of the process and the utilization rate of raw materials, reduces production costs, and combines 3D modeling to prepare high-temperature phase change thermal storage ceramics with arbitrarily complex structures.

[0027] The high thermal conductivity and high temperature phase change heat storage ceramic prepared by the present invention has a high filler content and a complete core-shell structure. The thermal conductivity reaches 40-60W / (m﹒K), the phase change latent heat reaches 340-400J / g, and the phase change latent heat retention rate is above 90% after cycling 300 times between 500 and 650°C. At the same time, it has certain mechanical properties, and the flexural strength reaches 35-50MPa. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a scanning electron microscope image of a high thermal conductivity, high temperature phase change heat storage ceramic prepared by the present invention. DETAILED DESCRIPTION

[0029] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.

[0030] Examples 1-5 all prepare high thermal conductivity and high temperature phase change thermal storage ceramics according to the following preparation method.

[0031] The preparation method comprises the following steps:

[0032] S1, adding aluminum powder or aluminum-based alloy powder to glucose solution, and hydrothermally reacting in a reactor at 160-200° C. for 2-8 hours to obtain carbon ball / boehmite-coated metal micropowder;

[0033] The metal powder coated with carbon sphere / boehmite is immersed in 60°C iron sol for 1 to 5 hours, and then the excess iron sol is removed, and the AlOOH / C / FeOOH coated microcapsule precursor is obtained by filtration and drying;

[0034] The Si content in the aluminum-based alloy powder is 10-12wt%.

[0035] S2. Evenly mix the microcapsules obtained in step S1 with an aluminum-containing binder to obtain a mixed raw material; the mass ratio of the microcapsules, the aluminum-containing binder and the catalyst is 70-99:1-30:0-3.

[0036] The aluminum-containing binder is aluminum silicon + magnesium, and the particle size of the aluminum-containing binder is 15-53 μm.

[0037] The catalyst includes one or more of ammonium chloride, nano iron powder, iron silicon nitride and platinum powder.

[0038] S3, printing the mixed raw materials into samples by 3D laser in a nitrogen atmosphere; the laser power is 30-150W, the scanning speed is 500-5000mm / s, and the scanning interval is less than the laser radius;

[0039] S4. Place the sample in a N2 atmosphere and heat it at a heating rate of 5°C / min, and keep it at 650-1200°C for 3-24h; then cool it to room temperature at a cooling rate of -5°C / min to obtain the high thermal conductivity and high temperature phase change thermal storage ceramic.

[0040] The specific process parameters and product performance of Examples 1-5 are shown in the following table:

[0041]

[0042]

[0043] It can be seen from the above table that the thermal conductivity of the high thermal conductivity and high temperature phase change thermal storage ceramic of the present invention can reach 40-60W / (m﹒K), and the phase change latent heat can reach 340-400J / g, which effectively ensures the high thermal storage density of the phase change thermal storage ceramic. At the same time, it has certain mechanical properties, and the bending strength reaches 35-50MPa.

[0044] Figure 1 This is a scanning electron microscope image of a high thermal conductivity and high temperature phase change thermal storage ceramic prepared by the present invention. Figure 1 It can be seen that a large amount of AlN is generated on the surface of the microcapsules and coated on the surface, and the gaps between the particles are also connected by AlN whiskers.

[0045] For matters not mentioned above, the prior art applies.

[0046] Although some specific embodiments of the present invention have been described in detail through examples, those skilled in the art should understand that the above examples are for illustration only and are not intended to limit the scope of the present invention. Those skilled in the art to which the present invention belongs may make various modifications or supplements to the specific embodiments described or replace them in a similar manner, but they will not deviate from the direction of the present invention or exceed the scope defined by the attached claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc. made to the above embodiments based on the technical essence of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing high thermal conductivity and high temperature phase change thermal storage ceramics, characterized in that: The steps include: S1, adding aluminum powder or aluminum-based alloy powder to glucose solution, and hydrothermally reacting in a reactor at 160-200° C. for 2-8 hours to obtain carbon ball / boehmite-coated metal micropowder; The metal powder coated with carbon sphere / boehmite is immersed in 60°C iron sol for 1 to 5 hours, and then the excess iron sol is removed, and the AlOOH / C / FeOOH coated microcapsule precursor is obtained by filtration and drying; S2, mixing the microcapsule precursor obtained in step S1 and the aluminum-containing binder uniformly to obtain a mixed raw material; S3, printing the mixed raw materials into samples by 3D laser in a nitrogen atmosphere; the laser power is 30-150W, the scanning speed is 500-5000mm / s, and the scanning interval is less than the laser radius; S4. Placing the sample in a N2 atmosphere for heat treatment and then cooling it to obtain the high thermal conductivity and high temperature phase change heat storage ceramic.

2. The preparation method according to claim 1, characterized in that The heat treatment in step S4 is to increase the temperature at a heating rate of 5°C / min, keep the temperature at 650-1200°C for 3-24h; and then cool to room temperature at a cooling rate of -5°C / min.

3. The preparation method according to claim 1, characterized in that: The mixed feed also includes a catalyst.

4. The preparation method according to claim 3, characterized in that: The catalyst includes one or more of ammonium chloride, nano iron powder, ferrosilicon nitride, and platinum powder.

5. The preparation method according to claim 3, characterized in that: The mass ratio of the microcapsule precursor, the aluminum-containing binder and the catalyst is 70-99:1-30:0-3.

6. The preparation method according to claim 1, characterized in that: The aluminum-containing binder includes one of aluminum powder and aluminum-based alloy powder.

7. The preparation method according to claim 1, characterized in that: The particle size of the aluminum powder or aluminum-based alloy powder is 40 to 53 μm.

8. The preparation method according to claim 1, characterized in that: The particle size of the aluminum-containing binder is 15 to 53 μm.

9. The preparation method according to claim 1, characterized in that: The content of Si in the aluminum-based alloy powder is 10-12 wt %.

10. A high thermal conductivity and high temperature phase change heat storage ceramic prepared by the preparation method according to any one of claims 1 to 9.